Mike Johansen’s Critical Discourse - Petrova, Tetiana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The article characterizes the features of M. Johansen critical discourse on the material of the texts of dictionary reviews. It is determined that the individual thinking style of the scientist, his creative approaches to solving certain problems are expressed during the critical evaluation of the works of other scientists. The relevance of the research is motivated by the need to analyze M. Johansen's reviews of dictionaries, which are a valuable component of his critical discourse, to understand and characterize the phenomenon of his linguistic personality as a reviewer.The purpose of this study is to characterize the features of dictionary criticism and the features of M. Johansen critical discourse based on the material of dictionary reviews.Dictionary review is a tool for improving the quality of national dictionary production and at the same time an integral genre that combines features of scientific communication, language criticism, and source studies, which involve examination and evaluation of dictionaries. The review genre is primarily presented in critical discourse.It is established that the analyzed reviews of dictionaries reveal the author's personality of the critic M. Johansen of the observant type (the term by Y. Shevelev), as well as represent him  as a reviewer with a deep and wide erudition and a high level of critical thinking.It is determined that the individuality of M. Johansen style of criticism is extremely expressive, partly with emotional and expressive connotations, which are connected with the expression of the reviewer's personal attitude to the analyzed material.It is found that M. Johansen critical discourse is a kind of intellectual laboratory, where he gives a part of himself, establishes the values ​​of dictionaries, and carries out their comparative analysis.The original evaluative constructions which are abundant in the reviews, sometimes presented with phraseological units that highlight the essence of the individual meanings of the linguistic personality of the critic, are traced.The main approach of M. Johansen to evaluating dictionaries is to postulate the concept of "loyalty" to the Ukrainian language and to strive to develop it on the basis of the modern developments and best achievements of national lexicography.